PELATIHAN KOMUNIKASI ASERTIF UNTUK MENCEGAH PERILAKU DAN KEKERASAN SEKSUAL PADA REMAJA - Dian Astrid Widyani; Magdalena Hanoum; Novita Dian Iva Prestiana (An-Nizam, 2022)
Adolescence is one of the stages of human development which is characterized by biological, cognitive and socio-emotional changes. Facing various changes in their lives, adolescents often experience emotional instability so that they are easily influenced by the environment, especially friends and various pornographic media. Adolescents need to be equiped with abilities that can protect themselves from sexual behavior and sexual violence. The purpose of carrying out these community service activities is to provide psychoeducation and socialization as well as training contained in the Community Service work program, namely psychoeducation or socialization on Healthy Internet (Pornography). Psychoeducation on Sexual Violence in Dating (KSDP) and Training on Self-Control in Adolescents with the theme Assertive Communication Training to Prevent Sexual Behavior and Violence in Adolescent to be applied in daily life to prevent sexual behavior and violence in adolescents. Training activities are carried out through workshops with interactive methods such as roleplay. The main targets in this community service implementation activity are teenagers who live on jl. Bandung B1/5 RT 01/010 Housing Bekasi Jaya Indah Mekarsari, East Bekasi, aged 15 to 21 years, namely Junior High School, Senior High School and College Student. A total of 17 teenage girls and 3 teenage boys. Adolescence is one of the stages of human development which is characterized by biological, cognitive and socio-emotional changes. Facing various changes in their lives, adolescents often experience emotional instability so that they are easily influenced by the environment, especially friends and various pornographic media. Adolescents need to be equiped with abilities that can protect themselves from sexual behavior and sexual violence. The purpose of carrying out these community service activities is to provide psychoeducation and socialization as well as training contained in the Community Service work program, namely psychoeducation or socialization on Healthy Internet (Pornography). Psychoeducation on Sexual Violence in Dating (KSDP) and Training on Self-Control in Adolescents with the theme Assertive Communication Training to Prevent Sexual Behavior and Violence in Adolescent to be applied in daily life to prevent sexual behavior and violence in adolescents. Training activities are carried out through workshops with interactive methods such as roleplay. The main targets in this community service implementation activity are teenagers who live on jl. Bandung B1/5 RT 01/010 Housing Bekasi Jaya Indah Mekarsari, East Bekasi, aged 15 to 21 years, namely Junior High School, Senior High School and College Student. A total of 17 teenage girls and 3 teenage boys.